Proteolysis modification targeting protein corona affects ultrasound-induced membrane homeostasis of saccharomyces cerevisiae: Analysis of lipid relative contributions on membrane properties - Zheng, Zi-Yi; Xie, Guo; Tan, Gui-Liang; Liu, Wen-Li (Frontiers in Microbiology, 2023)
Protein corona (PC) adsorbed on nanoparticles surface brings new research perspectives on the interaction between nanoparticles and microorganisms. Herein the time-varying proteolysis using cell-free protease extract from S.cerevisiae targeting wheat PC-coated Fe3O4 nanoparticles resulted in regular changes to the corona hydrodynamic diameters, ζ-potentials and surface hydrophobicity. Furthermore, remarkable disturbances of four S.cerevisiae membrane properties and membrane lipidomic remodeling in response to ultrasound + nano-Fe3O4@PC were observed with the prolonged time of PC proteolysis. Furthermore, the mapping relationship between lipids and membrane properties was establish using BP-ANN model combined with the approach of feasible virtual samples generation. Ergosterol, phosphatidylserine and phosphatidylinositol phosphate had the most substantial influence on membrane potential. For membrane fluidity, the contributions of ergosterol, phosphatidylethanolamines and phosphatidic acid separately accounted for 19.1%, 14.2% and 12.1%. The relative contributions of 6 lysolecithin on membrane oxidation and the dissipation of proton motive force remained limited.